Electron transfer dynamics and electrocatalytic oxygen evolution activities of the Co3O4 nanoparticles attached to indium tin oxide by self-assembled monolayers - Liu, Xuan; Tian, Qianhong; Li, Yvpei; Zhou, Zixiang; Wang, Jinlian; Liu, Shuling; Wang, Chao (Frontiers in Chemistry, 2022)
The Co3O4 nanoparticle-modified indium tin oxide-coated glass slide (ITO) electrodes are successfully prepared using dicarboxylic acid as the self-assembled monolayer through a surface esterification reaction. The ITO-SAM-Co3O4 (SAM = dicarboxylic acid) are active to electrochemically catalyze oxygen evolution reaction (OER) in acid. The most active assembly, with Co loading at 3.31 × 10−8 mol cm−2, exhibits 374 mV onset overpotential and 497 mV overpotential to reach 1 mA cm−2 OER current in 0.1 M HClO4. The electron transfer rate constant (k) is acquired using Laviron’s approach, and the results show that k is not affected by the carbon chain lengths of the SAM (up to 18 -CH2 groups) and that an increase in the average diameter of Co3O4 nanoparticles enhances the k. In addition, shorter carbon chains and smaller Co3O4 nanoparticles can increase the turn-over frequency (TOF) of Co sites toward OER. The Co3O4 nanoparticles tethered to the ITO surface show both a higher number of electrochemically active Co sites and a higher TOF of OER than the Co3O4 nanoparticles bound to ITO using Nafion.